Lessons :an autobiography - "Wang, An" (Massachusette, 1986)
This story of the man behind Wang Labs offers lessons about building a company, including managing growth in moderation, keeping the spark of innovation alive in a huge corporation, and standing up to an agressive competitor
Keywords: "Wang, An - Biography"